The cost of making wine: A Tuscan case study based on a full cost approach - Enrico Marone; Marco Bertocci; Fabio Boncinelli; Nicola Marinelli (Wine Economics and Policy)
This article×³s aim is to identify and quantify the connection between a winery business typology and its production cost per bottle to create benchmarks for managerial and organisational choices. Accounting data from wineries in representative areas of the Tuscan wine sector were collected with direct, face-to-face interviews. The data were processed using a cost accounting model elaborated by UniCeSV (Centre for the Strategic Development of the Wine Sector, University of Florence) to classify costs according to production phases and production factors. The study was completed using a hierarchical cluster analysis (HCA) approach to investigate the relation between cost structures and business typologies. The implementation of the cost accounting model and the HCA showed a strong relationship between how wineries are organised and how costs are structured. Moreover, the weight of geographical localisation (i.e., belonging to a specific denomination of origin) has proved to be a key determinant in the shape of the cost structures of wineries. Keywords: Wine production, Full cost analysis, Clustering